Prognostic factors that affect the response to topical treatment in patchy alopecia areata - Ucak, H.; Cicek, D.; Demir, B.; Erden, I.; Ozturk, S. (Wiley, 2014)
Background Alopecia areata (AA) is an organ-specific, T-cell-mediated autoimmune disease that is characterized by non-scarring hair loss. Objective We aimed to find the factors that may affect the response to topical therapy in AA. Methods The study included a total of 60 patients with AA and 30 healthy control patients. The AA patients were randomized into two groups. 40 patients used 0.05% clobetasol propionate cream, and 20 patients used petrolatum (placebo). Both groups applied topical treatments to their lesions twice daily for 12weeks. Results The mean extent of AA was 21.8816.75% in patients with autoantibodies and 12.16 +/- 13.55% in those who were negative for autoantibodies (P=0.021). Ophiasic pattern and nail involvement were observed more frequently in patients with atopy (P<0.05). Relapse was more frequent in patients with atopy (P=0.002) and nail involvement (P=0.02). Conclusions We observed that the presence of autoantibodies was associated with more extensive AA, and that ophiasic hair loss pattern and nail dystrophy were significantly associated with atopy. Topical clobetasol propionate treatment produced a modest advantage in hair regrowth as compared with placebo. Notably, atopic AA patients have a higher risk of relapse and redevelopment of AA after completing a course of topical corticosteroid treatment.
Keywords: Autoimmune-Disease; Antibodies; Profile; Onset; Pathogenesis; Singapore; Severity; Update; Muscle